The prince & me - Amin, Mark.; Amiel, Jack.; Begler, Michael; Fugate, Katherine, 1965-; Coolidge, Martha; Stiles, Julia, 1981-; Mably, Luke, 1976-; Miller, Ben, 1966-; Fox, James, 1939-; Richardson, Miranda; Nepomniaschy, Alex.; Cohen, Steven; et al. (Hollywood, Calif. : Paramount, 2004)
Paige is a college student at a university in Wisconsin where she hopes to attend medical school. One day, Paige meets a new student on campus, Eddie, who is obviously attracted to her. Paige and Eddie strike up a friendship which slowly turns into romance. Paige learns that Eddie is actually Prince Edward, heir to the throne of Denmark, who has come to Wisconsin to chase girls and enjoy himself away from the eye of the European press. Now Paige must decide if she wants to give up her dreams and ambitions, even if she gets her prince in return.
Special features: commentary by director Martha Coolidge; the lawn mower race of 'The prince & me'; inside the fairy tale: 'The prince & me'; 7 deleted/extended scenes; alternate ending; gag reel; theatrical trailer.
Director of photography, Alex Nepomniaschy ; editor, Steven Cohen ; music, Jennie Muskett ; costume designer, Magali Guidasci ; production designer, James Spencer.
Julia Stiles, Luke Mably, Ben Miller, James Fox, Miranda Richardson.
MPAA rating: PG; for some sex-related material and language.
DVD, Region 1, full screen (1.33:1) presentation; Dolby Digital, DTS.
Closed-captioned.
Keywords: Women college students -- Wisconsin -- Drama; Princes -- Denmark -- Drama; Man-woman relationships -- Drama; Feature films; Romantic comedy films; Films for the hearing impaired